Nonlinear and Quantum Optics on the Nature of Sugar Emission Excited by the First Harmonic of a Nd Laser - Oleshko V. I. Vladimir Ivanovich; Tsipilev V. P. Vladimir Papilovich; Yakovlev A. N. Aleksey Nikolaevich; Murastov G. V. Gennadiy Viktorovich; Alekseev N. A. Nikolay Anatoljevich (2018, 2018)
Title screen